S93 Toll-like receptor 2 has a tumour suppressor function in murine non-small cell lung cancer. (12th November 2019) - Millar, FR; Quintanilla, A; Hari, P; Muir, M; Arends, M; Frame, M; Wilkinson, S; Acosta, JC
Abstract : Background: Lung cancer is the leading cause of cancer related deaths worldwide. Patients typically present with late stage metastatic disease, making curative treatment impossible in the majority of cases. The value of targeting early stage disease has been widely recognised to improve overall mortality. Oncogene induced senescence (OIS) is an innate cell cycle arrest program instigated following the activation of oncogenes, and is a well known tumour suppressor mechanism. OIS is abundant in pre-malignant lesions in murine lung cancer models, however is lost during the progression to malignancy. We have recently identified a regulatory role for Toll-like receptor 2 (Tlr2) in oncogene-induced senescence 1, however the functional relevance of this has yet to be established in vivo . Methods: To determine the effect of Tlr2 signalling during non-small cell lung cancer (NSCLC) progression, we used mice heterozygous for the loxp-STOP-loxp-Kras G12D allele (Kras LSL-G12D/+ ), allowing lung specific activation of mutant Kras G12D signalling upon intranasal infection with Cre-recombinase expressing adenovirus (Adeno-CMV-Cre). Kras LSL-G12D/+ mice were interbred with Tlr2 -/- mice to generate a Kras LSL-G12D/+ ; Tlr2 -/- strain. 1.5 x 10 7 PFU of Adeno-CMV-Cre was delivered intranasally and mice were culled 12 weeks later. Tumour burden, proliferative markers (Ki67) and senescence markers (p21) were assessed by immunohistochemistry. Results: Tumour burden was significantly increased in Kras LSL-G12D/+ ;Tlr2 -/- mice in comparison to Kras LSL-G12D/+ ;Tlr2 +/+ mice (p<0.01). This was associated with an increased proliferative index (p<0.001) and reduced p21 staining (p<0.001), indicating a reduced inability to undergo senescence. Conclusions: We have identified an in vivo functional role for Tlr2 in the suppression of murine lung cancer progression. By understanding the mechanisms regulating this early stage tumour suppressor process we may be able to develop biomarkers of early disease to better stratify lung cancer screening approaches. Reference: Hair P, et al . The innate immune sensor Toll-like receptor 2 controls the senescence associated secretory phenotype. Sci Adv . 2019 Jun 5;5(6).